Balla Károly fogarasi lelkész fogsága és halála - András Jakab CSŰRÖS; Ferenc TÖMÖSKÖZI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2025)
The Imprisonment and Death of Károly Balla, Pastor of Fogaras. The study aims to present – largely based on archival sources – one of the traumatic events of the First World War through the life of a Reformed pastor. Despite the great wave of refugees, Károly Balla looked after the town and the values of the parish. He put his family and the parish’s most important movable property in a cart and set off for Cluj-Napoca. Károly Balla’s life was shattered, along with that of his family’s. He was eventually taken away by the Romanian soldiers, and only with great difficulty was he able to regain his freedom, even temporarily...